Sociological methods for solving current practical issues of higher education: action research - Soroka , Y. (New Collegium, 2020)
The purpose of this article is to review the characteristics and principles of research in action and actualization in this context of sociological methods and relevant research competencies of teachers. Research in action is presented as one that can be used by lecturers to obtain the necessary information about their current students, which is necessary to compensate for socio-cultural barriers to the introduction of student-centered education, choice of teaching methods, increase student motivation, general and subject competencies. Demonstrated that action research are relevant in the perspective of socio-cultural and other aspects (globalization, economic) changes in modern society.The most important features and principles of action research in the field of education are presented. It is emphasized that their purpose is determined not by the priorities of science to create a universal pedagogical theory, but by the specific tasks of practice in a particular audience or class. The principles of action research are developed and widely studied in sociology, directly related to the methods of obtaining data - surveys, interviews, focus group interviews, document analysis, observation, as well as the formulation of the research problem, setting goals and objectives of the study, and questions validity and reliability of research data. Action research procedures demonstrate the use of sociological methodology for the tasks of direct educational practice, so action research as a field of educational activity is not yet widely represented in Ukraine, can receive support and resources from the sociological field. The interaction of action research and sociology is demonstrated through the author’s experience in studying students’ expectations from the course. The conditions for distance learning during a pandemic are becoming a new field for the development of research practices in action. The task of creating an appropriate learning environment, adequate to the objectives of the course and the nature of the student audience, are more noticeable in the distance, when communication sessions with students are limited in time, and meeting through the screen narrows the field for observing students in the classroom and using teaching intuition.